Understanding the current plummeting phenomenon in microbial fuel cells (MFCs). (April 2021) - Li, Dunzhu; Shi, Yunhong; Gao, Fei; Yang, Luming; Li, Siyuan; Xiao, Liwen
Highlights: The mechanism of current plummeting phenomenon was elucidated. Current, anode surface area and chamber volume were found as the determinants for current plummeting occurrence. A robust empirical equation was developed for simple-fast prediction of current plummeting occurrence. Abstract: Current plummeting occurs when the organic matter concentrations decrease to the threshold levels during the operation of microbial fuel cells (MFCs) system. As both electrical energy production rate and organic matter removal rate are significantly lower after it occurs, the threshold organic matter concentrations at the current plummeting point (CODCPP ) largely determine to what extent the MFCs could efficiently remove organic matter and harvest energy from the wastewater. The CODCPP varies with different MFCs. In this study, a combination of experimental and theoretical approaches was used to investigate the effect of different components on CODCPP . It was found that the CODCPP was affected by the current, chamber structure and anode brush loading. The logarithm of CODCPP has linear relationship with the logarithm of ratio of external current to anode chamber volume. The findings will facilitate the design of MFCs to efficiently decrease the effluent organic matter concentrations to meet the discharge standard and to gain stable current generation from wastewater with low organic matter concentrations.